Agricultural waste management generated by agro-based industries using biotechnology tools - D. Sivakumar; P. Srikanth; P. Ramteke; J. Nouri (Global Journal of Environmental Science and Management)
The amount of agricultural waste generated by agro-based industries such as palm oil, rubber, and wood processing plants have more than tripled. Selangor, Perak, and Johor account for 65.7 percent of the total number of recognised pollution sources in the manufacturing and agro-based sectors. Livestock dung is another major cause of pollution, contributing significantly to increase pollution levels in the environment. Large portion of agro-industrial waste is untreated and unused, it is frequently disposed of by replicating or dumping then again off the cuff landfilling.  These untreated wastes wreak havoc on natural change by releasing ozone-depleting chemicals. Aside from that, the usage of fossil fuels is also leading to an increase in ozone-depleting compounds. Agro-waste is a huge environmental hazard in the current epidemic situation. The management of agro-waste and the conversion of agro-waste into a usable product through the application of biotechnological technologies in agriculture are receiving a lot of attention in today''s world. Solid state fermentation is the finest approach for converting agro-waste into valuable bio products among biotechnological instruments.  Various agro-wastes such as wheat straw, barley straw, cotton stalks, sunflower stacks, and oil cakes from various agriculture goods, as well as major horticulture wastes such as apple, mango, orange peels, and potato peels, were used to create beneficial products in this review.  All aspects of the production of industrial products from various agro-waste by using microorganisms such as Amycolatopsis Mediterranean, Xanthomonas campestries, and Aspergillus niger producing biopolymers such as polysaccharides, similar to starch, cellulose, agar, hemi-celluloses, gelatin, alginate, and carrageenan are covered in the current revels. Yeasts and cyanobacteria are commonly employed to make bio-lipids, whereas Bacillus species are utilised to make proteins and bio-enzymes. Cucumber and orange strips, on the other hand, have recently been employed to create proteins and bio-enzymes.  As a result, this review covers the many forms of agro-wastes and their by-products as well as biotechnological technologies used to treat them.